Photocatalysis of Cd-doped ZnO synthesized with precipitation method - Phattranit Dumrongrojthanath (2019)
© 2019, The Nonferrous Metals Society of China and Springer-Verlag GmbH Germany, part of Springer Nature. ZnO particles doped with 0 mol%–5 mol% Cd dopant were successfully synthesized by a precipitation method. The as-synthesized products were characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), photoluminescence (PL) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) coupled with an energy-dispersive X-ray (EDX) spectroscopy and transmission electron microscopy (TEM). The precursors showed weight loss at 35–700 °C caused by phase transformation and evaporation processes. The as-synthesized products were specified as hexagonal wurtzite ZnO. The crystallite size of ZnO samples doped with 0 mol%–5 mol% Cd gradually increased with the increase in Cd content. The photocatalytic activities of 0 mol%–5 mol% Cd-doped ZnO samples were evaluated through photodecolorization of methylene blue (MB) under ultraviolet (UV) radiation. In this research, ZnO doped with 3 mol% Cd shows the best photocatalytic activity in degrading of MB molecules as much as 89% within 240 min.